Patterns of plumage colouration, genetic and morphological variation in mountain blackeye, Chlorocharis emiliae (Aves: Zosteropidae) from Malaysian Borneo - Mohamad Fizl Sidq, Ramji (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study comprised ofthree main phylogeographical components that elucidate the patterns of variation among isolated populations of mountain blackeye subspecies from major Borneo mountain tops including Chlorocharis emiliae emiliae on Mount Kinabalu (KK), c. e. trinitae on Mount Trus Madi (TM) and C. e. moultoni on Mount Murud (MD) and Mount Mulu (ML). The following components which assimilate plumage colour polymorphism, population genetic diversity and morphometric analysis were evaluated by three comparative methods utilising Munsell colour scoring system, DNA sequencing and discriminant function analysis (DFA) respectivelyY he overall fmdings revealed incongruent display between genetic and phenotypic differentiation that eventually rejects the classical taxonomic classifications of C. e. trinitae (Harrison, 1956). Rooting on the fmdings of plumage colour component, the best plumage indicator was probably displayed within the belly (BY) region compared to the other scored plumage characters such as crown (CR), supercilium (SC), auricular (AU), mantle (MT), rump (RP), breast (BR) and vent (VT). Critical to this, the total plumage scores (TPS) were detached between the low TPS (3-7) in C. e. emiliae and the high TPS (9-14) of C. e. moultoni while C. e. trinitae mirrors an intermediate colour variation (TPS = 8-11) between the darker pigmented C. e. emiliae and the brighter and more intense pigments of C. e. moultoni. As for the morphometric analysis, tarsus length (TR) and bill length (BL) were identified as the best predictors from nine character loadings observed which also included bill depth (BD), bill width (BW), head bill (HB), wing length (WL), wing span (WS), tail length (TA) and total length (TL). For population genetic analysis, a total of 490 base pair (bp) consisting 22 haplotypes from 40 mountain blackeye sequences were inferred from the mitochondrial DNA (mtDNA) Cytochrome Oxidase 1 (COl). Both maximum-likelihood (ML *) and Bayesian inference trees as well as the minimum-spanning network (MSN) showed monophlyletic haplotype groupings with two mam clusters representing haplo-group 1 of the Sabah populations (KK and TM) and haplo-group 2 of the Sarawak populations (MD and ML). Haplotype 4 was shared between KK and TM thus implying greater genetic resemblances despite abrupt phenotypic dissimilarities between these neighbouring popUlations. Coupled to this, the strong gene flow occurrences between KK.-TM with relatively considerable values within MD-ML further delineates the regional partitioning by the proposed genetic break of the northern-southern populations. This may indicate that there has been some long separation between both regional popUlations that featured two distinctive phenotypic forms of C. e. emiliae and C. e. moultoni, in which the MD and KK populations were derived as potential ancestral popUlations of the recently diverged C. e. trinitae on TM and C. e. moultoni of ML population. Also, the population divergence time estimates primarily dated the Pleistocene epoch during the extreme climatic events which ultimately influenced the dispersal of ancestral populations to its neighbouring mountain refuge. The phenotypic emergence of C. e. trinitae as an intermediate clinal variation of C. e. emiliae and C. e. moultoni probably designate an excellent geographical speciation with gene flow model that underpin the rather complex but interesting evolutionary perspectives into the much debated subspecies status. In conclusion, this study had profoundly emphasized on the significance of avian phylogeographic studies within the South,.East Asian region, particularly ofthe Borneo montane avifauna.